Therapeutic Potential of the Nitrite-Generated NO Pathway in Vascular Dysfunction - Madigan, Michael; Zuckerbraun, Brian (Frontiers in Immunology, 2013)
Nitric oxide (NO) generated through L-arginine metabolism by endothelial nitric oxide synthase (eNOS) is an important regulator of the vessel wall. Dysregulation of this system has been implicated in various pathological vascular conditions, including atherosclerosis, angiogenesis, arteriogenesis, neointimal hyperplasia, and pulmonary hypertension. The pathophysiology involves a decreased bioavailability of NO within the vessel wall by competitive utilization of L-arginine by arginase and ‘eNOS uncoupling.’ Generation of NO through reduction of nitrate and nitrite represents an alternative pathway that may be utilized to increase the bioavailability of NO within the vessel wall. We review the therapeutic potential of the nitrate/nitrite/NO pathway in vascular dysfunction.